Political Environment and Privatization Prices - Alberto Chong; Alejandro Ria\~no (Inter-American Development Bank, Research Department, 2006)
This paper studies the link between the political and institutional context and privatization sales prices. The latter serves as a measure for assessing the relative performance of the privatization goals. Whereas this link has been studied theoretically, there are very few, if any, empirical papers on this relationship. Using data from 308 privatizations around the world and applying a cross-country approach (including instrumental variables), we find that, while the overall political regime does not matter much for prices, the political processes beyond the basic regime do matter. Institutional context also produces a significant impact on prices. Both results are robust to changes in specification.
Keywords: 330; Privatisierung; Preis; Vergleich; Welt